전기방사법을 이용한 PCL/MWCNTs 나노섬유 제조 - 최정미; Jung Mi Choi; 장현철; Hyun Chul Jang; 현재영; Jae Young Hyeon; 석중현; Jung Hyun Sok (대한금속·재료학회지, 50(10), 2012)
The uniform and highly smooth nanofibers of biocompatible poly (ε-caprolactone) (PCL) composited with different contents of multiwalled carbon nanotubes (MWCNTs) were successfully prepared by electrospinning. Experimental parameters were MWCNTs addition to a PCL solution and applied voltages. The topographical features of the composite nanofibers were characterized by scanning electron microscopy and its electrical properties were measured by a four-point probe method. The surface resistance gradually decreased with an increasing content of MWCNTs in PCL fibers because of the excellent electrical conductivity of MWCNTs. The nanofiber diameter could be regulated by varying the solution viscosity and voltages. Our results establish that this kind of electrospinning PCL/MWCNTs nanofibers with the control of fiber diameter and electrical conductivity may be a promising candidate for the application of scaffolds in tissue engineering.